VARIASI UKURAN KARBON TEMPURUNG KELAPA SEBAGAI ALAT KONTROL KELEMBABAN - E. Taer; S. Aiman; Sugianto Sugianto; R. Taslim (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Studied on humidity control at testing room has been carie out by using carbon from coconut shell. The carbon is then milled using a ball milling equipment and sieved to obtained various of particle size of a variation of the size of 10 ð›m, 53 ð›m, and 38 ð›m. The results showed that forthe carbon with particle size 100 Î¼mshow the humidity of testing room was 88%, carbon 53 Î¼m produce humidity of 86%, and carbon 38 Î¼m produce humidity of 85%, Without carbon the humidity in the testing room show of 90%. X-ray diffraction characterization of the carbon 38 Î¼m showed a decrease on the interlayer spacing (d002 and d100), stack height (Lc), and the stack widht (La) compared with the carbon of 100 Î¼m. Scanning electron microscopy (SEM) shows the carbon surface morphology, particle size and pore distribution of carbon. Kararakterisasi EDX results showed levels of carbon contained in coconut shell by 93.19%. Testing of carbon as humidity control device showed the maximum results when using carbon 38 Î¼m compared to 53 Î¼m carbon, and carbon 100 Î¼m. Key words: coconut shell karbon, characterization, activated carbon, humidity.